Validasi handout fisika pembelajaran kontekstual pada materi gelombang berjalan stasioner bunyi dan cahaya kelas XI SMA/MA - Khairul Ilham Saf; Yurnetti Yurnetti (Universitas Negeri Padang, 2019)
Education is a learning process for humans to be able to understand and make more critical in thinking. Contextual learning is a learning concept that can help teachers associate material taught with real-world situations and encourage students to make connections between their knowledge and application in their lives. Curriculum development conducted by the government is expected to be able to face the times, be able to overcome complex challenges and be able to apply skills and knowledge in their lives. However, the reality in school teaching materials used by students is not optimal and does not vary. The solution that can be given to overcome this problem is to make teaching materials in the form of Contextual Learning Physics Handouts. This research aims to determine the validity of Contextual Learning Physics Handouts. The steps taken in research are Research and Development (R&D). The object of research is the contextual physics learning handout on the material traveling wave, stationary, sound and light class XI SMA/ MA. The instrument used to collect data is validity sheets from experts. The data analysis technique used is descriptive statistical analysis. Based on research and data analysis that has been done can be presented with research results. The average value of contextual physics learning handouts is 83.74 with very high validity criteria. So, it can be concluded that the Contextual Learning Physics Handout is at a very high level of validity.